Analysis of combined operation of electro-osmetic dewatering and mechanical expression - Jami, Mohammed Saedi; Iwata, Masashi (2009)
This paper presents results of experimental work carried out to study and analyze the combined operation of electro-osmotic dewatering (EOD) and mechanical expression (ME) by use of the Terzaghi-Voigt combined model for considering creep deformation of the material. The EOD-ME process combines the advantage of electro-osmosis and mechanical dewatering, resulting in reduced void ratio compared to individual operation. The basic differential equation based on the model is solved analytically by assuming that both an electro-osmotic pressure gradient Epg and a modified consolidation coefficient Ce of the material are constant, resulting in the equation of solid compressive pressure in the material as a function of time and position. The analysis also leads to the equation of the average consolidation ratio Uc, which is a measure of the progress of dewatering; this equation can describe well the empirical results under various conditions. The large water content ofbentonite slurry can be reduced well by the EOD-ME combined operation.